1990
DOI: 10.1203/00006450-199001000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Growth Retardation: Altered Hepatic Energy and Redox States in the Fetal Rat

Abstract: ABSTRACT. We determined the extent to which ligating both maternal uterine arteries affects fetal hepatic energy and redox states in the fetal rat. Bilateral maternal uterine artery ligation on d 18 of the rat's 21.5-d gestation significantly inhibits fetal growth; sham surgery limits growth to a lesser extent. Within 12 h of surgery and persisting to d 19, small-for-gestational age (SGA) fetuses had significantly diminished ATPIADP and adenylate charge ratios, whereas sham fetuses had values intermediate betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
47
1
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 16 publications
7
47
1
1
Order By: Relevance
“…As glycogen storage in fetal brains is minimal (27), the supply of free glucose via glycogenolysis from glycogen storage tissues such as the liver and kidney plays an important role in the survival of the fetus during times of stress. It has been demonstrated that accumulation of fetal hepatic glycogen is decreased in animal models of FGR (25), and in our study we also observed that FGR brains had lower glycogen content. Taken together, these experimental data suggest that FGR brains may have a low tolerance to the effects of undernutrition and adaptive glycogenolysis.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…As glycogen storage in fetal brains is minimal (27), the supply of free glucose via glycogenolysis from glycogen storage tissues such as the liver and kidney plays an important role in the survival of the fetus during times of stress. It has been demonstrated that accumulation of fetal hepatic glycogen is decreased in animal models of FGR (25), and in our study we also observed that FGR brains had lower glycogen content. Taken together, these experimental data suggest that FGR brains may have a low tolerance to the effects of undernutrition and adaptive glycogenolysis.…”
Section: Discussionsupporting
confidence: 72%
“…In general, glucose transportation across the placenta and the blood-brain-barrier is facilitated by carrier-mediated diffusion that is dependent on the concentration gradient. Ogata et al (25) showed that growth-retarded fetuses had significantly diminished plasma glucose concentrations 10 and 240 min after uterine artery ligation, which recovered to normal ranges by the 21st gestational day. Our results support the hypothesis that fetal glycogen degradation with resultant hyperglycemia ensures an adequate supply of substrates to vital tissues such as the brain, and provides, at least, some measure of fetal tolerance to interruptions in placental oxygen transport (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is abundant evidence that liver is a target for programming. The exposure to uteroplacental insufficiency alters the expression of genes encoding enzymes involved with hepatic energy production, 51 decreasing hepatic oxidative phosphorylation 52 and affecting liver glucose transport. 53 The impaired suppression of endogenous hepatic glucose production is an important component of the peripheral insulin resistance associated with type 2 diabetes.…”
Section: Evidence For Liver Programmingmentioning
confidence: 99%
“…To test our hypothesis, we performed bilateral uterine artery ligation on pregnant Sprague-Dawley rats to induce uteroplacental insufficiency and subsequent growth restriction. Fetal rats in this well-characterized model are significantly lighter than controls that undergo identical anesthesia and sham surgery, and litter size does not differ between control and IUGR groups (4,(15)(16)(17)(18)(19)(20)(21). BCKAD activity was subsequently measured in fetal liver with a radiochemical assay.…”
mentioning
confidence: 99%